1962
DOI: 10.1017/s0022112062001226
|View full text |Cite
|
Sign up to set email alerts
|

Effect of natural convection on stability of flow in a vertical pipe

Abstract: If water is heated or cooled while flowing through a vertical pipe with a laminar motion, the velocity profile will differ from the parabolic shape for isothermal flow due to density variations in the fluid. If a constant heat flux is used at the wall and if the changes in temperature affect only the density appearing in the gravity term of the equations of motion, a condition is attained far downstream in the heat-transfer section such that there is no further change in the velocity profile. The shape of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
0

Year Published

1964
1964
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(47 citation statements)
references
References 1 publication
7
40
0
Order By: Relevance
“…A following brief review is emphasised on the flow reversal phenomenon and the flow instability in a vertical tube. For such configuration, the pioneers works by Hanratty and colleagues in the early sixties [3,4] have clearly shown that the non-isothermal flow appears to be highly unstable and may undergo its transition from a steady laminar state to an unstable one at rather low Reynolds number. The unstable flow structure, which was not turbulent, has shown, in fact, the 'new equilibrium' state that consisted of large scale, regular and periodic fluid motions.…”
Section: Introductionmentioning
confidence: 99%
“…A following brief review is emphasised on the flow reversal phenomenon and the flow instability in a vertical tube. For such configuration, the pioneers works by Hanratty and colleagues in the early sixties [3,4] have clearly shown that the non-isothermal flow appears to be highly unstable and may undergo its transition from a steady laminar state to an unstable one at rather low Reynolds number. The unstable flow structure, which was not turbulent, has shown, in fact, the 'new equilibrium' state that consisted of large scale, regular and periodic fluid motions.…”
Section: Introductionmentioning
confidence: 99%
“…The critical ratio increases with increasing a from 15.9 at CI = 0.25 to 99.1 at CY = 1.50. For ratio values larger than the critical, flow separation and instability have been observed experimentally for Newtonian liquids (12) and would be expected to occur also for non-Newtonian liquids. It appears that for downflow as well as upflow, the limiting stable N G J N R~ value is lower for pseudoplastic than for dilatant fluids.…”
Section: Numerical Resultsmentioning
confidence: 83%
“…Koppel and Smith (14) have shown the fallacy of the second assumption by proving that it leads to the conclusion that velocity profiles can be calculated without recourse to the momentum equation, and the calculated profiles are independent of the gravity field. This assertion conflicts with the experimental results of Hanratty, Rosen, and Kabel ( 4 ) , and Scheele and Hanratty (17). Thus, a radial velocity component must exist.…”
Section: Literature Surveymentioning
confidence: 80%